Adults' recollections of support and closeness during adolescence amid interparental conflict - Groper, Galit (Violence and victims, 2025)
This study examined adults’ memories of childhood exposure to interparental conflict, including support for and closeness to each parent. Closeness and support were explored based on three dimensions: dyadic concordance types of intimate partner violence (father to mother, mother to father, or both), form of violence (verbal or physical), and sex. This study featured 548 Israeli adults who completed a retrospective questionnaire on their parents’ interparental violence, their level of support for each parent during conflict, and their closeness to each parent. The results revealed a notable pattern: adolescents exhibited greater support and closeness toward nonviolent parents compared to violent parents, irrespective of the form of violence. Sex differences emerged across types and severity of violence. Theoretical and practical implications of the findings are discussed.